Radiation asymmetries during the thermal quench of massive gas injection disruptions in JET. (19th November 2015) - Lehnen, M.; Gerasimov, S.N.; Jachmich, S.; Koslowski, H.R.; Kruezi, U.; Matthews, G.F.; Mlynar, J.; Reux, C.; de Vries, P.C.
Abstract: Radiation asymmetries during disruption mitigation by massive gas injection (MGI) can result in substantial first wall heat loads in ITER and have, therefore, to be minimised. This paper gives a first analysis of the relation between the magnetohydrodynamic instabilities governing the thermal quench (TQ) and the toroidal distribution of the radiated power during MGI experiments at JET. It is found that the radiation asymmetry is closely linked to the toroidal phase of the mode. The mode phase, on the other hand, is influenced by the injection itself, with the O-point of the mode being displaced towards the injection location. The development of a component during the TQ has been identified from temperature and soft x-ray measurements. The observations suggest that the TQ mechanism during MGI is the same as for density limit disruptions. High energy plasmas show a much smaller peaking compared to Ohmically heated plasmas. Neon injection has the tendency towards lower radiation peaking compared to argon injection.